Efficacy of DEPO-MGA® in feedlot heifers - Jack G. Riley; Ronald V. Pope; L. O'Neill (Kansas Agricultural Experiment Station Research Reports, 1987)
Three levels of melengestrol acetate (30, 60, and 90 mg) injected subcutaneously as a liquid (DEPO-MGA ®) in the ear of heifers yielded high performance results comparable to feeding 0.5 mg of MGA per head daily. Heifers fed 0.5 mg MGA daily gained 6% faster and were 11% more efficient than heifers not receiving MGA. This study will be pooled with trials from 13 other locations in the U.S. to determine if further development and FDA clearance of DEPO-MGA ® will be pursued by the Upjohn Company.
Keywords: Cattlemen& #x27; s Day; 1987; Kansas Agricultural Experiment Station contribution; no. 87-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 514; Beef; DEPO-MGA ®; Feedlot heifers